Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(B=\frac{19^{31}+5}{19^{32}+5}< \frac{19^{31}+5+90}{19^{32}+5+90}=\frac{19^{31}+95}{19^{32}+95}=\frac{19\left(19^{30}+5\right)}{19\left(19^{31}+5\right)}=\frac{19^{30}+5}{19^{31}+5}=A\)
b, Ta có: \(\frac{1}{A}=\frac{2^{20}-3}{2^{18}-3}=\frac{2^2.\left(2^{18}-3\right)+9}{2^{18}-3}=4+\frac{9}{2^{18}-3}\)
\(\frac{1}{B}=\frac{2^{22}-3}{2^{20}-3}=\frac{2^2\left(2^{20}-3\right)+9}{2^{20}-3}=4+\frac{9}{2^{20}-3}\)
Vì \(\frac{9}{2^{18}-3}>\frac{9}{2^{20}-3}\)\(\Rightarrow\frac{1}{A}>\frac{1}{B}\Rightarrow A< B\)
c, Câu hỏi của truong nguyen kim
![](https://rs.olm.vn/images/avt/0.png?1311)
1)
Dễ thấy \(B=\dfrac{10^{19}}{10^{19}-3}>1\)
\(\Rightarrow B=\dfrac{10^{19}}{10^{19}-3}>\dfrac{10^{19}+2}{10^{19}-3+2}=\dfrac{10^{19}+2}{10^{19}-1}=A\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\left(3\frac{1}{2}-2x\right).3\frac{1}{3}=7\frac{1}{3}\)
\(\left(\frac{7}{2}-2x\right).\frac{10}{3}=\frac{22}{3}\)
\(\frac{7}{2}-2x=\frac{11}{5}\)
\(2x=\frac{13}{10}\)
\(x=\frac{13}{20}\)
Vậy ...
b) \(\frac{4}{9}x=\frac{9}{8}-0,125\)
\(\frac{4}{9}x=1\)
\(x=\frac{9}{4}\)
Vậy...
A=1+3+3^2+...+3^20 (1)
3A=3+3^2+3^3+...+3^21 (2)
lấy (2) trừ (1) ta đc 2A=3^21-1
từ B=3^21:2=>2B=3^21
do đó 2B - 2A = 3^21 - (3^21 - 1)
=> 2.(B - A) = 1
=> B - A = 1/2